2016
DOI: 10.29252/ijrm.14.9.557
|View full text |Cite
|
Sign up to set email alerts
|

GnRH agonist trigger versus hCG trigger in GnRH antagonist in IVF/ICSI cycles: A review article

Abstract: Routinely, a bolus of 5.000-10.000 IU human chorionic gonadotropin (hCG) is used for the final follicular maturation and ovulation as a standard method. HCG has the same effect of luteinizing hormone (LH) with long half-life. It has the long lutheotrophic effect which increases the risk of ovarian hyper stimulation syndrome (OHSS). Recently, gonadotropin-releasing hormone agonist (GnRH-a) trigger has been used for the induction of final follicular maturation and ovulation with the aim of reducing the OHSS risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 84 publications
0
23
2
1
Order By: Relevance
“…It may reflect a different timing of oocyte maturation leading to an earlier activation pathway. Although the lower pregnancy rates with GnRHa trigger are usually related to its luteolytic effect and its negative effect on endometrial receptivity [24][25][26], the slightly lower pregnancy rate in the GnRHa trigger group in our study may be related to decreased embryo quality as well.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…It may reflect a different timing of oocyte maturation leading to an earlier activation pathway. Although the lower pregnancy rates with GnRHa trigger are usually related to its luteolytic effect and its negative effect on endometrial receptivity [24][25][26], the slightly lower pregnancy rate in the GnRHa trigger group in our study may be related to decreased embryo quality as well.…”
Section: Discussioncontrasting
confidence: 52%
“…Matching creates quasi-experimental samples, reducing potential bias caused by the imbalance between the two study groups. GnRHa triggering is usually given to prevent ovarian hyperstimulation syndrome (OHSS) in hyper-responder patients such as women with polycystic ovarian syndrome (PCOS) [24]. Matching of the cycles for maternal age, number of oocytes retrieved, and peak E2 levels was performed in attempt to isolate the effect of the triggering itself on the morphokinetic parameters of the embryos while reducing possible intrinsic maternal physiologic and metabolic influence on the kinetics of embryo development…”
Section: Discussionmentioning
confidence: 99%
“…In the last two decades, GnRH-a has been a trigger factor for the final follicle maturation, which significantly reduced the incidence rate of OHSS clinically [ 8 , 9 ]. However, many studies have reported that GnRH-a trigger protocol is prone to luteal insufficiency [ 10 ], resulting in the decrease of clinical pregnancy rate and the increase of early abortion rate [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…GnRH-a can stimulate FSH surge and LH surge. FSH surge has a beneficial effect on oocyte maturation and causes cumulus expansion of the oocyte [16][17][18][19][20]22].…”
Section: Discussionmentioning
confidence: 99%